Economic Growth and Environmental Pollution in Tanzania: An Environmental Kuznets Curve Analysis (Tanzania Journal for Population studies and Development, 2023)
The creation of a long-term linkage between economic growth and environmental protection is a subject of an ongoing discussion among scholars and policymakers. The relationship between environmental quality and economic growth is viewed from two different angles. According to the first, it is impossible to protect the environment and increase the economy at the same time since doing so will inevitably result in the extinction of either one or both. The other contends that economic advancement and higher environmental quality can be achieved simultaneously since increasing economic growth raises income levels, which in turn increases the demand for environmental protection. However, there is a disagreement over how much environmental resources should be exploited to support rapid economic expansion. This study used the approach of the Environmental Kuznets Curve (EKC) hypothesis to investigate the relationship between economic growth and environmental pollution in Tanzania. Tanzania’s economy annual data from 1970 to 2018 was used in the ARDL bounds testing for cointegration procedures. The evidence suggests that environmental pollution and economic growth have a U-shaped relationship, which rules out the existence of a traditional EKC in Tanzania. Like in many emerging economies, environmental pollution is anticipated to rise in Tanzania if economic expansion continues beyond a threshold level. The U-shaped link between economic growth and environmental pollution is important for policy formulation because both economic growth and a clean environment are welfare-enhancing; therefore, it is possible to have two policies that are mutually supportive rather than antagonistic. This can be achieved by having a proper environmental, legal, and institutional frameworks.